Shear strength parameter determination for the single plane of weakness criterion: Implications for wellbore stability. Issue 3 (October 2020) - Ma, Tianshou; Qiu, Yi; Liu, Diancheng; Liu, Yang; Zhu, Gongsheng; Peng, Nian
Abstract: Wellbore stability is a classic rock mechanics problem encountered during drilling and completion, which costs the drilling industry more than $100 million per year worldwide. The failure criterion is a very important aspect of the wellbore stability analysis. Accordingly, for shale rich in bedding, fissures, joints, and cuts, we often use the single plane of weakness criterion to describe the compressive shear strength. The anisotropic strength of a rock depends on the strength of the rock matrix and the weak plane (i.e., cohesive strength of the matrix, friction angle in the matrix, cohesion of the weak plane, and friction angle in the weak plane). However, directly and accurately determining the compressive shear strength parameters of the rock matrix and the weak plane using the conventional least square and molar stress circle methods is difficult because of the difference between the rock matrix and the weak plane. This study uses the grid search algorithm to quickly match the optimal matrix cohesion, matrix internal friction angle, weak plane cohesion, and weak plane internal friction angle through the published triaxial test data of two sets of anisotropic rocks. The four parameters of the compressive shear strength materials obtained by the grid search algorithm are used to predict the results, which are very consistent with the experimental results. The correlation coefficient ( R 2 ) above 0.98 is enough to meet the engineering requirements. Taking a shale gas well in the Sichuan Basin as an example, a collapse pressure prediction model is finally established by combining the grid search method to determine the material parameters of the compressive shear strength, shear wellbore instability model, and SWP criterion. Consequently, the model results are found to be in good match with the engineering practice.